Answer:
The above expression is simplified as [tex](\frac{2n^3}{3n^4} )^2 = \frac{4}{9n^2}[/tex]
Step-by-step explanation:
Here, the given expression is:
[tex](\frac{2n^3}{3n^4} )^2[/tex]
Laws of Exponents:
1. [tex]\frac{x^m}{x^n} = x^{(m-n)}[/tex]
2. [tex](\frac{x}{y} )^k = \frac{x^k}{y^k}[/tex]
3.[tex]x^m. x^n = x^{m +n}[/tex]
using the above results, we get:
[tex](\frac{2n^3}{3n^4} )^2 = (\frac{2n^{3-4}}{3} )^2\\=(\frac{2n^{(-1)}}{3}) ^2\\=(\frac{2}{3n} )^2 = (\frac{2^2}{(3n)^2} )\\=\frac{4}{9n^2} \\\implies(\frac{2n^3}{3n^4} )^2 = \frac{4}{9n^2}[/tex]
Hence, the above expression is simplified as [tex](\frac{2n^3}{3n^4} )^2 = \frac{4}{9n^2}[/tex]